Ion Flux of Confined Ion Mixtures - Marañon Di Leo, Julio (2023)
The transport of ions in a confined solution at nano-meter scale is critical for the function of inorganic and biological membranes. Then, it is important to study the effect of nano-confinement of ion transportation by computer simulation. To focus on the effect of nano-confinement, it is useful to investigate ion transport by that means. To reduce computational time, simple electrolyte models can be used. The structure of the water molecules surrounding an ion is described by the ion-atom radial distribution function (RDF). Ion size trends are those to be expected on intuitive grounds, in addition to the position and height of the first peaks. The height of the first peak diminished as cation size increased, thus implying a weakening of the cation. The purpose of this study was to apply an external electric field at the ends of a flexible nanopores contained configured as an electrolyte model under periodic boundary conditions, with molecular dynamics (MD). The results show several ion currents. The electrolyte model was composed of three Na+/K+ concentration ratios in aqueous solutions. For both cations, the radial distribution function (RDF) g(s) does not depend neither on voltage nor cation mixtures. Na+ current-voltage (I-V) curves change for low Na+ concentrations only.